Case Report: short stature, kidney anomalies, and cerebral aneurysms in a novel homozygous mutation in the PCNT gene associated with microcephalic osteodysplastic primordial dwarfism type II - Petraroli, Maddalena; Percesepe, Antonio; Piane, Maria; Ormitti, Francesca; Castellone, Eleonora; Gnocchi, Margherita; Messina, Giulia; Bernardi, Luca; Patianna, Viviana Dora; Esposito, Susanna Maria Roberta; Street, Maria Elisabeth (Frontiers in Endocrinology, 2023)
We report the case of a boy (3yr and 7 months) with severe growth failure (length: - 9.53 SDS; weight: -9.36 SDS), microcephaly, mental retardation, distinctive craniofacial features, multiple skeletal anomalies, micropenis, cryptorchidism, generalized hypotonia and tendon retraction. Abdominal US showed bilateral increased echogenicity of the kidneys with poor corticomedullary differentiation, and a slightly enlarged liver with diffuse irregular echotexture. A first MRI of the brain performed at presentation showed areas of gliosis with encephalomalacia and diffused hypo/delayed myelination, and a thinned appearance of the middle and anterior cerebral arteries. Genetic analysis evidenced a novel homozygous variant of the pericentrin (PCNT) gene. PCTN is a structural protein expressed in the centrosome that plays a role in anchoring protein complexes, regulating mitotic cycle and cell proliferation. Loss-of-function mutations of its gene are responsible for microcephalic osteodysplastic primordial dwarfism type II (MOPDII), a rare inherited autosomal recessive disorder. This boy died at 8yr because of an intracranial hemorrhage due to a cerebral aneurism associated with the moyamoya malformation. Unlike cases previously published, intracranial anomalies and kidney findings were evidenced very early in life. This case suggests to include MRI of the brain with angiography since diagnosis in the follow-up of MODPII.